Some bright nowhere : a novel [large type] - Packer, Ann, 1959- (Harper Large Print, an imprint of HarperCollinsPublishers, 2026)
"Eliot and his wife Claire have been happily married for nearly four decades. They've raised two children in their sleepy Connecticuttown and have weathered the inevitable ups and downs of a long lifespent together. But eight years after Claire was diagnosed with cancer, the end is near, and it's time to gather loved ones and preparefor the inevitable. Over the years of Claire's illness, Eliot has willingly--lovingly--shifted into the role of caregiver, appreciatingthe intimacy and tenderness that comes with a role even more layered and complex than the one he performed as a devoted husband. But ashe focuses on settling into what will be their last days and weeks together, Claire makes an unexpected request that leaves him reeling. In a moment, his carefully constructed world is shattered"--